Diffusion of The Internet : A Cross-Country Analysis - Andrés, Luis 2020- (The World Bank, 2007)
This paper analyzes the process of Internet diffusion across the world using a panel of 199 countries during 1990-2004. The authors group countries in two categories-low and high-income countries-and show that the Internet diffusion process is well characterized by an S-shape curve for both groups. Low-income countries display a steeper diffusion curve that is equivalent to a right shift of the diffusion curve for high-income countries. The estimated diffusion curves provide evidence of a "catching-up" process, although a very slow one. The paper explores the determinants of Internet diffusion at the country level and across the same income groups. The most novel finding is that network effects seem to be crucial-the number of Internet users in a country in a given year is positively associated with the number of users in the previous year. The findings also show that the degree of competition in the provision of Internet service contributes positively to its diffusion, and there are significant positive language externalities